Evaluating an inclusive program for promoting equal-status participation in classrooms with high sociolinguistic diversity: diversity valuation and multilingual cooperative activities - Buchs, Céline; Margas, Nicolas; Hascoët, Marine (Frontiers in Psychology, 2023)
The inclusion of students with diverse heritage languages is an emerging issue in all OECD countries due to the global rise in international migration. With regard to their large cultural and linguistic heterogeneity, primary school classes in the French-speaking region of Switzerland are extraordinary grounds to develop inclusive teaching in context of high diversity. This research-action aims to enhance students' status among their peers and promote equal-status participation in academic activities in such classes. The research perspective focuses on valuing diversity within classes and emphasizing students' linguistic competence through cooperative activities.The tested inclusive program places value on linguistic diversity and proposes multilingual cooperative activities that involve students' family languages and require the contributions of all students. The research was conducted over the course of a school year, involving 3rd-4th grade students. It compared the evolution students' status among peers (being chosen as a groupmate for play and work) from the beginning to the end of the school year in four classes with the inclusive program (N = 77) and four control classes without the inclusive program (N = 62). The results indicated expected changes in status: status increased in classes with the inclusive program, while it decreased in classes without the program. Moreover, the intervention specifically supported the status of vulnerable pupils. In classes with the inclusive program, students with initially low status experienced the greatest improvement, whereas in control classes, there was no correlation between initial status and changes in status. At the beginning of the school year, across all classes, students with low status participated passively, experiencing higher levels of exclusion and displaying more discrete behavior, highlighting potential initial status-problems issues. This pattern persisted in control classes without the inclusive program, where low-status students were more likely to remain passive, while initially high-status students were more likely to become leaders. In contrast, with the inclusive program, the relationship between status and participation diminished by the end of the year. These findings suggest that the inclusive program contributed to reducing status-related problems and promoting more equal-status participation.